Penyuluhan Kesehatan Penyuluhan Kesehatan Pentingnya Pengetahuan kesehatan Reproduksi Bagi Remaja Di Era Moderen Di SMA N 1 Kotamobagu - Ningsi, Suci Rahayu; Patonegan, Gita Sandy; Sibuah, Siska; Pobela, Winni; Fauzan, Moh. Rizki (Cattleya Darmaya Fortuna, 2025)
Reproductive health is guidance related to physical, mental, or social disabilities, not just the absence of disease or disability but all matters related to the reproductive system, its functions, and processes. Understanding reproductive health for adolescents is very important. A lack of knowledge among adolescents regarding reproductive health can lead to issues with their reproductive health. Problems that may arise if adolescents do not have sufficient knowledge about reproductive health include sexually transmitted diseases and infections. The purpose of this knowledge is to assess the level of understanding adolescents have regarding reproductive health. This will be conducted through interactive lectures and question-and-answer sessions accompanied by the distribution of leaflets.